2008
DOI: 10.1128/jvi.01011-08
|View full text |Cite
|
Sign up to set email alerts
|

Different Types of nsP3-Containing Protein Complexes in Sindbis Virus-Infected Cells

Abstract: Alphaviruses represent a serious public health threat and cause a wide variety of diseases, ranging from severe encephalitis, which can result in death or neurological sequelae, to mild infection, characterized by fever, skin rashes, and arthritis. In the infected cells, alphaviruses express only four nonstructural proteins, which function in the synthesis of virus-specific RNAs and in modification of the intracellular environment. The results of our study suggest that Sindbis virus (SINV) infection in BHK-21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
193
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(204 citation statements)
references
References 65 publications
(80 reference statements)
8
193
3
Order By: Relevance
“…However, in the last few years, our understanding of the alphavirus RNA replication mechanism has undergone some modifications. It was demonstrated that for some of the alphaviruses, such as SINV and VEEV, replication complexes are formed at the plasma membrane, and a major fraction of them remain there, even at later stages of the infection and continue to function as sites of viral RNA synthesis (49)(50)(51). Thus, RNA replication and its packaging into virions are likely to be more closely compartmentalized than we previously thought.…”
Section: Discussionmentioning
confidence: 75%
“…However, in the last few years, our understanding of the alphavirus RNA replication mechanism has undergone some modifications. It was demonstrated that for some of the alphaviruses, such as SINV and VEEV, replication complexes are formed at the plasma membrane, and a major fraction of them remain there, even at later stages of the infection and continue to function as sites of viral RNA synthesis (49)(50)(51). Thus, RNA replication and its packaging into virions are likely to be more closely compartmentalized than we previously thought.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, the recruitment of the minus strand for replication inside cells appears to happen with a very low efficiency or not at all. Based on several lines of evidence, it is generally thought that the minus strands are present in infected cells in dsRNA form in complex with the plus strands (Gorchakov et al, 2008;KulasegaranShylini et al, 2009;Mai et al, 2009;Spuul et al, 2010). The inability of the minus strand to serve as a template in any RNA synthesis might therefore also mean that for plusstrand synthesis the replicase would require a (partially) dsRNA template.…”
Section: Discussionmentioning
confidence: 99%
“…nsP3 is the most enigmatic of all nsPs, with unclear yet essential roles in alphavirus RNA replication (11). nsP3 is highly phosphorylated (12,23), is part of the viral replication complex (RC) (5), and has been shown to interact with Ras-GAP SH3 domain-binding proteins (G3BP1 and G3BP2) in two independent coimmunoprecipitation studies (3,7). Infection with another Togaviridae family member; rubella virus, has been shown to alter the distribution of host cell G3BP, suggesting that G3BP plays an important role in the outcome of viral infection (16).…”
mentioning
confidence: 99%